Remedies for European growth problem - Viren Matti (Aboa Centre for Economics (ACE), 2015)
This paper deals with the slowdown of economic growth in Europe. For that purpose, we focus on factors that affect the long-run growth path of different economies. Special emphasis is paid to institutional and structural factors that are often assumed to affect aggregate growth: functioning of labor markets, availability of labor and capital, and the size of government. For more explicit measures, we use the data on profit rates, average working hours, various dependency ratio indexes, tax rates, other measures of the size of government, and measures of price competitiveness. Empirical analysis makes use of cross-country panel data from EU15 countries for 1971-2014. Estimation results suggest that profitability and competitiveness do indeed constitute the main determinants of growth. However, also other variables like average working hours and the size of government appear to affect growth in an important manner. All in all, slowdown of growth in Europe does not appear to be beyond reasonable explanations. Thus, more ambitious growth rates may be achieved with well-designed policies.
Keywords: O40; O43; 330; growth; working hours; taxes; competitiveness